A Study of the Ionic Liquid-Based Ultrasonic-Assisted Extraction of Isoliquiritigenin from Glycyrrhiza uralensis. (1st October 2020) - Hao, Jingwei; Liu, Jiahui; Zhang, Lei; Jing, Yunrong; Ji, Yubin
Abstract : We successfully extracted isoliquiritigenin from Glycyrrhiza uralensis through the utilization of an ionic liquid-based ultrasonic-assisted extraction (ILUAE) approach. Briefly, we utilized the solution of 1-butyl-3-methylimidazolium bromide ([BMIM]Br) as solvent and optimized key ILUAE parameters such as solid-liquid ratios, concentrations of ionic liquids, and the times of ultrasonication. Based on a single-factor experiment, we utilized the response surface method (RSM) approach to optimize the extraction procedure. The approach revealed that the optimal energy consumption time was 120 min, with the ultrasonic extraction temperature of 60°C. Using these optimized parameters together with the solid-liquid ratio (dried G. uralensis powder: [BMIM]Br of 0.3 mol/L) of 1 : 16.163 and the [BMIM]Br of 0.3 mol/L, we achieved a 0.665 mg/g extraction yield. Overall, these findings thus indicate that we were able to effectively use ILUAE as an efficient approach to reliably extract isoliquiritigenin in a reproducible and environmentally friendly manner.